Herpes Simplex Virus 1 (HSV-1) ICP22 protein directly interacts with cyclin-dependent kinase (CDK)9 to inhibit RNA polymerase II transcription elongation. - Zaborowska, J; Baumli, S; Laitem, C; O'Reilly, D; Thomas, P; O'Hare, P; Murphy, S (Public Library of Science, 2014)
The Herpes Simplex Virus 1 (HSV-1)-encoded ICP22 protein plays an important role in viral infection and affects expression of host cell genes. ICP22 is known to reduce the global level of serine (Ser)2 phosphorylation of the Tyr1Ser2Pro3Thr4Ser5Pro6Ser7 heptapeptide repeats comprising the carboxy-terminal domain (CTD) of the large subunit of RNA polymerase (pol) II. Accordingly, ICP22 is thought to associate with and inhibit the activity of the positive-transcription elongation factor b (P-TEFb) pol II CTD Ser2 kinase. We show here that ICP22 causes loss of CTD Ser2 phosphorylation from pol II engaged in transcription of protein-coding genes following ectopic expression in HeLa cells and that recombinant ICP22 interacts with the CDK9 subunit of recombinant P-TEFb. ICP22 also interacts with pol II in vitro. Residues 193 to 256 of ICP22 are sufficient for interaction with CDK9 and inhibition of pol II CTD Ser2 phosphorylation but do not interact with pol II. These results indicate that discrete regions of ICP22 interact with either CDK9 or pol II and that ICP22 interacts directly with CDK9 to inhibit expression of host cell genes.